Primary identification of Microbacterium spp. encountered in clinical specimens as CDC coryneform group A-4 and A-5 bacteria. - Funke, G (1995)
Over nearly two decades, 13 yellow- or orange-pigmented, fermentative gram-positive rods belonging to the genus Microbacterium were encountered in clinical specimens. All 13 strains, 10 of which came from blood cultures, were initially identified as CDC coryneform group A-4 and A-5 bacteria according to the scheme of Hollis and Weaver for the identification of gram-positive rods. The clinical isolates were compared with the type strains of the six species constituting the genus Microbacterium as well as with three Microbacterium strains isolated from hospital environments. By biochemical methods only 5 of 13 clinical isolates could be identified to species level. Peptidoglycan analysis proved to be a valuable tool for differentiation between Microbacterium spp. and related genera, whereas cellular fatty acid analysis did not allow species identification within the genus Microbacterium. The 22 Microbacterium strains studied were, in general, susceptible to antimicrobial agents used in the treatment of infections caused by gram-positive rods. This report is the first one concerning the isolation of Microbacterium strains from clinical specimens. The sources as well as the mode of transmission remain to be established.